Esoteric Aspects of Said Nursi’s Interpretation of Tawhid: Influence and Thought - Islam, Muhammad Thoriqul; Rahma, Raisya Miftakhul; Marjany, Nawa (Institut Agama Islam Negeri (IAIN) Keiri, 2024)
Nowadays, Muslims need a concept of monotheism that is not only academic but also increases faith. Nursi divided the idea of monotheism into two dimensions: birth monotheism and true monotheism. These concepts focused on growing faith related to current life. Both interpretations of exoteric and esoteric monotheism verses were critical to understand. The research explored Nursi's esoteric approach to monotheistic verses and their influence on Islamic theology. The qualitative research design employed the literature review method by obtaining data from journals, proceedings, books, and documentaries. Then, data were analyzed using content analysis techniques and esoteric and historical approaches. The research results indicated that Nursi's esoteric interpretation of monotheistic verses aligned with other sufi mufassirs but had two significant differences. First, Nursi's esoteric approach, especially in tafakkur, provided concrete examples that could be felt physically. Second, as a member of the Naqshbandi Tariqa, Nursi consistently referred to asmā' al-ḥusnā and associated it with manifestations reflected in all entities when interpreting the Qur'an. Nursi's interpretation of monotheistic verses in Islamic theological thought became more dominant at the international level. Meanwhile, at the national level, the influence was more socio-religious. Nevertheless, Nursi's interpretation remains essential in addressing religious realities in Indonesia.